CONSUMPTION PATTERN AND CONSUMER PREFERENCE FOR VALUE- ADDED FISH AND FISH PRODUCTS IN NORTH ZONE OF INDIA - Sabat, Sunil; Sharma, Arpita; Salim, Shyam (Journal of Indian Fisheries Association, 2008)
Present paper attempts to analyze consumption pattern and consumer preferences towards value-added fish and fish products in north zone of India. Results reveal that socio economic variables affect consumption of value-added fish and fish products. A total of 49 percent respondents were of middle age group 35 to SO years). All were literates except 1 percent from the rural area. All were purchasing fish at least once in 15 days. A total of 90 percent respondents in rural, 11 percent in semi urban and 50 percent in urban area were unaware of value-added fish and fish products. About 10 percent of respondents had consumed it, out of which most were from urban area. Demand analysis by Cobb Douglas (CD Demand function; revealed that when price of fish, price of the substitutes, income of family and family size were used as independent variables, variation in demand of fish explained by CD Demand function was about 39 percent in urban area, 24 percent in semi urban area and 22 percent in rural area. From Garette ranking technique major problems in fish consumption found were irregular supply, lack of fresh fish, high price and presence of bones in fish. While lack of awareness, unavailability, no preference and unacceptable taste were major problems for consumption of value-added fish and fish products. Keywords: Consumption, consumer preference, value-added fish products.